Differences Between Men and Women Aged 65 and Older in the Relationship Between Self‐Reported Sleep and Cognitive Impairment: A Nationwide Survey in Taiwan. Issue 10 (14th September 2016) - Chiu, Hsiao‐Yean; Lai, Fu‐Chih; Chen, Pin‐Yuan; Tsai, Pei‐Shan
Abstract : Objectives: To examine the prevalence of self‐reported sleep disturbances and cognitive impairment in men and women aged 65 and older and to determine sex‐specific effects on the relationship between self‐reported sleep and cognitive impairment. Design: A secondary data analysis from the 2009 Taiwan National Health Interview Survey. Participants: Individuals aged 65 and older (N = 2, 413, n = 1, 094 men, n = 1, 319 women). Measurements: Subjective sleep characteristics including sleep duration, difficulty initiating sleep, difficulty maintaining sleep, early‐morning awakening, daytime sleepiness, difficulty breathing during sleep, habitual snoring, and daytime napping were measured using survey questions. The Mini‐Mental State Examination was used to identify cognitive impairment. Results: The prevalence of cognitive impairment was 16.3% for men and 27.1% for women. Men and women with cognitive impairment had higher prevalence of self‐reported sleep disturbances than those without. There was a significant effect of the interaction between sex and difficulty breathing during sleep on cognitive impairment (adjusted odds ratio (aOR) = 0.39, 95% confidence interval (CI) = 0.20–0.77). In men, difficulty breathing during sleep (aOR = 2.31, 95% CI = 1.39–3.84), habitual snoring (aOR = 2.30, 95% CI = 1.49–3.54), and prolonged sleep duration (> 8.5 hours) (aOR = 1.95, 95% CI = 1.11–3.43) correlated significantly with cognitive impairment. In women, only prolonged sleep duration (>8.5 hours) was associated with higher likelihood of cognitive impairment (aOR = 2.32, 95% CI = 1.33–4.03). Conclusion: This nationwide survey confirmed sex differences in the association between various self‐reported sleep disturbances and cognitive impairment in people aged 65 and older.